Effect of Puguntano Extract (Curanga Fel-Terrae Merr.) on hs-CRP Level in Newly Diagnosed Type 2 Diabetes Mellitus Patient - Hartono Apriliasta Purba; Santi Syafril; Dharma Lindarto (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Inflammation is one of the factors that associated with insulin resistance which causes type 2 diabetes mellitus (T2DM). Inflammation can be measured by using high sensitivity C-reactive protein (hs-CRP), a quantitative measurement of CRP concentration. Puguntano is a plant that traditionally used for antidiabetic treatment found in North Sumatera. The objective of this study is to know the effect of Puguntano extract on hs-CRP level in newly diagnosed T2DM patient.METHODS: The study was a randomized controlled clinical trial on 24 newly diagnosed T2DM patients. Subjects were divided into 2 groups. The first group was given Puguntano extract with starting doses at 100 mg daily, then the dose was increased in titration up to a maximum dose of 2x100 mg daily depending on blood sugar level monitoring. Meanwhile, the other group (which serves as a control group) was given metformin with starting doses at 500 mg daily, then the dose was increased in titration up to a maximum dose of 3x500 mg per day depending on blood sugar level monitoring. The hs-CRP and HbA1c are assessed at the baseline and after 12 weeks of treatment.RESULTS: The hs-CRP level was decreased in Puguntano group by 1.41 (-7.54-0.52) (p=0.06) and decrease by 0.58 (-7.86-33.41) (p=0.695) in metformin group. There was no difference in hs-CRP level between the two groups (p=0.630).CONCLUSION: Puguntano extract showed the effect of lowering HbA1C and hs-CRP level in T2DM patients, although it was not statistically significant.KEYWORDS: type 2 diabetes mellitus, hs-CRP, puguntano